2014
DOI: 10.1093/molbev/msu141
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Positive Selection in Seven Ant Genomes

Abstract: The evolution of ants is marked by remarkable adaptations that allowed the development of very complex social systems. To identify how ant-specific adaptations are associated with patterns of molecular evolution, we searched for signs of positive selection on amino-acid changes in proteins. We identified 24 functional categories of genes which were enriched for positively selected genes in the ant lineage. We also reanalyzed genome-wide data sets in bees and flies with the same methodology to check whether pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
126
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(142 citation statements)
references
References 176 publications
9
126
6
1
Order By: Relevance
“…In order to characterize the signal of positive selection, we used the log-likelihood ratio test statistic (∆lnL) of H 1 to H 0 models with or without positive selection, from the branch-site model (Zhang et al 2005) as precomputed in Selectome on filtered alignments , and as used in (Roux et al 2014;Daub et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In order to characterize the signal of positive selection, we used the log-likelihood ratio test statistic (∆lnL) of H 1 to H 0 models with or without positive selection, from the branch-site model (Zhang et al 2005) as precomputed in Selectome on filtered alignments , and as used in (Roux et al 2014;Daub et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A long-standing debate in the field of sociogenomics is the importance of conserved genes vs. novel genes in social evolution (2,3). Researchers have tried to address this question primarily by either looking for signatures of positive selection associated with the evolution of sociality (43,44) or by looking for genes that are differentially expressed between different morphological and behavioral castes (45,46). An alternative approach is to find genes with specific functions in social behavior and to examine their evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that genes encoding proteins in the insect immune response are exceptionally likely to evolve by repeated positive selection (Schlenke and Begun 2003;Sackton et al 2007;Lazzaro 2008;Obbard et al 2009;Keebaugh and Schlenke 2012;Roux et al 2014); here, we focus particularly on rates of gene gain and loss. Several lines of evidence suggest that the M. domestica immune response is unusual, at least when compared with the standard Dipteran model D. melanogaster.…”
Section: Discussionmentioning
confidence: 99%